Avaliação da funcionalidade e implicações na qualidade de vida de pessoas com hemofilia no estado do Amazonas - Simão, Naamy Keely da Silva (2023)
Hemophilia is a coagulopathy caused by deficiency in clotting factors VIII (hemophilia A) and IX (hemophilia B). Clinical manifestations are evidenced by spontaneous bleeding and intra- articular bleeding known as hemarthrosis. Patients with this disease may present loss of function for certain activities and may suffer impacts that are still unknown in the assessment of functionality and quality of life. Therefore, this study aimed to evaluate the functionality and quality of life of people with hemophilia. Methodology: 27 individuals with hemophilia A and 3 with hemophilia B, male, aged 18 years and over, treated at Fundação HEMOAM, were evaluated. Clinical data collection was carried out using a semi-structured questionnaire. The clinimetric instruments Functional Independence Scale for Haemophilia (FISH), Hemophilia Joint Health Score (HJHS) 2.1, Hemophilia Activities List (HAL) and Hemophilia-Specific Quality of Life Index (Haem-A-Qol) were used to assess the functional capacity of the patient, joint health, daily activities and quality of life of the study population. Results: patients were divided into two groups, according to the severity of the disease, into mild and moderate hemophilia (Group 1 [G1]), with 12 individuals, and severe hemophilia (Group 2 [G2] with 18 individuals. The average age for both groups it was 34 years. The severe group presented more cases of elbow hemophilic arthropathy (p=0.0455). G1 presented a significantly higher score in the evaluation of the FISH and HAL instrument, when compared to G2 (p=0.029 and p=0.005, respectively). Regarding HJHS, G1 had a lower mean score when compared to G2 (p=0.007). No statistically significant differences were observed when comparing the mean scores of the Haemo-A-Qol instrument between the groups. Conclusion: Patients with severe hemophilia presented more musculoskeletal changes with a high degree of joint and functional impairment than people with mild/moderate hemophilia. Although our findings are promising, we believe that more studies are needed so that a treatment plan can be developed. personalized physiotherapeutic treatment, according to the limitations of each individual, as this is the first study to evaluate the patient's functional capacity, joint health, daily activities and quality of life in people with hemophilia treated in the State of Amazonas